APAP Overdose - Richard Stair (Association of American Medical Colleges, 2007)
Abstract The is a simulation case for the recognition of an acetaminophen (APAP) overdose in the emergency department. The case requires an appropriate evaluation; knowledge of when lab studies are indicated and their proper interpretation; and, the management and disposition of a simulated patient. Faculty observation of the student and/or resident on these tasks enables evaluation of their clinical skills and knowledge of how to appropriately manage toxic ingestion independently.